Digital Book Hindu-Buddhist Kingdom in Palembang Based on Flipbook Maker for High School Students - Dominikus Doni Petun; Saefur Rochmat; Zulkarnain Zulkarnain (AL-ISHLAH: Jurnal Pendidikan, 2023)
Teaching materials are learning tools that are used with the help of tools that facilitate the delivery of material during the learning process at school. A platform called Flipbook Maker provides open-access e-learning in the form of digital books. The purpose of this research is to evaluate the feasibility and effectiveness of Flipbook Maker-based learning media for e-learning. For class X SMA students, teaching materials were made in the form of digital books about the Kingdom of Sriwijaya with case studies at a junior high school in Sorong Regency. Development research with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation, is the research method used. Material experts, media experts, and linguists assigned “fit” scores to the research team's product during development. During the implementation phase, the researcher conducted tests with class X students of the school. Students in the Try Out One-to-One and Small Group Try Out groups evaluated the results of this implementation phase using the "very suitable" criteria. Finally, the evaluation results show the effectiveness of the product by showing an increase in student learning outcomes of 34.41%. This shows how effective digital books on the history of the Srivijaya Kingdom based on flipbook maker are for learning. The limitations of this research are the schools studied were only one school, and have different geography and demographics. Furthermore, the Flipook Maker learning media is only used on certain topics in history subjects whose results are not necessarily the same if used in the same or other subjects.